Some Elements Of Organizational Culture And Its Contributionship With Alleviating The Occupational Pressures Of The Workers In Sports Institutions .- A Field Study On The Administratives At The Directorate Of Youth And Sports - Adrar- - Dine, Chouaib; Ouchene , Bouzid (sports creativity, 2025)
Some elements of organizational culture and its contributionship with alleviating the occupational pressures of the workers in sports institutions. The goal of the study: Recognize the reality of organizational culture in the Algerian sports institutions; on the grounds that we are a Muslim society and should have a positive organizational culture institutions reflect his mastery and his love and devotion to his work. The Sample: A simple random sample consisting of 63 administrators -working at the Directorate of Youth and Sport and some sports facilities in the province of Adrar . - The results obtained: - The organizational culture is the key determinants of the success or failure of organizations. - The effective role of organizational culture derives from its importance and its functions. - The Formulation of the desired goals of the organization should be done by all workers, because the burden falls on them to achieve